THE EFFECT OF THE USE OF A MODEL FOR PREVENTING THE URINARY TRACT INFECTION ON THE LENGTH OF STAY IN PATIENTS WITH URINARY CATHETERIZATION IN A FEMALE MEDICINE WARD - Danthamrongkul, Phetcharat (JOURNAL OF THE POLICE NURSES AND HEALTH SCIENCE, 2020)
This quasi-experimental research was aimed to examine the effect of the use of a model for preventing the urinary tract infection on the length of stay in patients with urinary catheterization in a female medicine ward, Police General Hospital. Twenty female medical patients were purposively selected by inclusion and exclusion criteria, divided into the experimental group and the control group, 10 patients in each group. The instruments were the handbook of the prevention of the urinary tract infection, the questionnaire for general data collection, and the length of stay record form. Data were analyzed using mean, and standard deviation. The result showed that the average lengths of stay after using the model for preventing the urinary tract infection was less than the length of stay before using it (M = 18.10, SD = 13.63 and M = 22.63, SD = 17.00, respectively). The average lengths of stay after using the model for preventing the urinary tract infection was less than the average lengths of stay after receiving the routine nursing care (M = 18.10, SD = 13.63 and M = 19.30, SD = 13.69, respectively).